Determination of the diagnostic accuracy of rapid molecular assays for diagnosis of bloodstream infections in Pietersburg Hospital, Limpopo Province in South Africa - Maswanganyi, N. A. (My University, 2025)
Background Bloodstream infections (BSIs) are infections caused by the presence of viable microorganisms in the bloodstream and are an essential cause of morbidity and mortality, especially among immunocompromised individuals. Blood culture is still considered the gold standard for diagnosing BSI; however, prolonged turnaround times limit its use for rapid clinical decision-making. Rapid molecular techniques such as BioFire FilmArray Blood Culture Identification 2 (BCID2) and metagenomics sequencing offer faster turnaround time for pathogen detection than blood cultures, in which bacteria, fungi, and their resistance profiles are detected. Aim This study aimed to evaluate the diagnostic accuracy of rapid molecular assays for the identification of pathogens that causes bloodstream infections at Pietersburg Hospital in Limpopo Province, South Africa. Objectives Compare the effectiveness of VITEK2 and BCID2 in identifying pathogens present in positive blood culture samples. Metagenomics was used to resolve the discrepant results between the VITEK2 and BCID2. To assess the sensitivity, specificity, and overall diagnostic accuracy of the BCID2 and metagenomics in relation to the VITEK2. Methods This prospective diagnostic cross-sectional study was conducted at Pietersburg Hospital, Polokwane, Limpopo Province, South Africa. Participants included patients suspected of BSI from various regional hospitals and clinics of Limpopo Province. Blood samples sent to the National Health Laboratory Service (NHLS) from May to December 2023 were included. Blood culture bottles were incubated in a BacT/ALERT 3D system. Positive cultures were processed using VITEK 2 and BCID2, with discrepancies resolved by 16s metagenomics sequencing. Data were analyzed using SPSS (v29.0.0.0) and MedCalc (v22.026). Results Of the 247 samples, 78% (193/247) were Gram-negative bacteria, 17% (43/247) Gram-positive bacteria, and 4% (11/247) yeast. The ICU and paediatric units contributed 34% (83/247) and 29% (72/247) of samples, respectively. A total of 72% (179/247) were monomicrobial, while 28% (68/247) were polymicrobial. A total of nine off-panel organisms were detected in monomicrobial while seven were detected in polymicrobial samples. BCID2 achieved sensitivity, specificity, and accuracy rates of 95.7%, 95.5%, and 96%, respectively. CTX-M was the most common resistance gene (40%), while van A/B and VIM were rare (0.5% each). Metagenomics confirmed BCID2 in 72% of cases and VITEK 2 in 48%, detecting additional off-panel pathogens. Conclusions The BioFire FilmArray Blood Culture Identification 2 test gave a very good diagnostic performance with 96% and a faster detection of pathogens in 60 minutes, making it appropriate in emergency cases. VITEK 2 had a better diagnostic performance but relatively slower and surpassed BCID2 in some pathogens. Metagenomics sequencing, being the most comprehensive technique, confirmed 72% of results from BCID2 and identified novel ones. These findings highlight the complementary roles of BCID2, VITEK 2 and metagenomics in optimizing bloodstream infection diagnosis in poor resource settings
Thesis (M. Sc. (Medical Sciences)) -- University of Limpopo, 2025
Keywords: Bloodstream infections; Molecular diagnostics; Rapid assays; Blood culture Identification 2 (BCID2); VITEK 2; Metagenomics sequencing; Pietersburg Hospital; Bloodborne diseases; Molecular diagnosis; Metagenomics